Plagiarism: what kind of implications in higher education? - Braga, Inês (2016)
This research aims to reflect on ethical issues in the teaching-learning process in portuguese higher education in the context of Bologna, in particular the troubling reality of plagiarism practiced by students. To relate this issue with information literacy (IL) is inevitable, as at several international standards of IL, the question of ethics, copyright and plagiarism recurs. We highlight in the literature review, some investigations that focus on these matters, although of crucial importance, but wich don’t have had, in our view, adequate attention or the most appropriate practical action to deal with them. From a PhD research, carried out in a portuguese polytechnic higher school, focusing on eight undergraduate degrees in the areas of Accounting, Information Science, Human Resources, Design, Hotel Management and Engineering, we will stand out some results and interpretations of a study on IL and training for IL, highlighting, among others, the question of ethics and plagiarism, wich are regarded by different actors of the educational process. Through data gathering instruments - online questionnaires applied to teachers and students of these undergraduate degrees - and interviews ministered to the course coordinators and the librarian of the institution, there is enough material to conclusions betting on the need for a formal and continuing training, with collaborative actions between the educational agents and institutional reinforcement and impact.